Chances of geotourism development in the Colca and the volcanoes of Andagua Geopark (Peru) - Galas, Andrzej (2017)
Trabajo presentado en: 17th international scientific conference on earth & geosciences SGEM 2017, Section Ecology and Environmental Protection, Albena, Bulgaria, 29 June - 5 July, 2017.